Sustained delivery of biomolecules from gelatin carriers for applications in bone regeneration - Song, Jiankang; Leeuwenburgh, Sander Cg (Therapeutic delivery, 2014)
Local delivery of therapeutic biomolecules to stimulate bone regeneration has matured considerably during the past decades, but control over the release of these biomolecules still remains a major challenge. To this end, suitable carriers that allow for tunable spatial and temporal delivery of biomolecules need to be developed. Gelatin is one of the most widely used natural polymers for the controlled and sustained delivery of biomolecules because of its biodegradability, biocompatibility, biosafety and cost-effectiveness. The current study reviews the applications of gelatin as carriers in form of bulk hydrogels, microspheres, nanospheres, colloidal gels and composites for the programmed delivery of commonly used biomolecules for applications in bone regeneration with a specific focus on the relationship between carrier properties and delivery characteristics.